HUBUNGAN PENGETAHUAN PERAWAT DENGAN PERILAKU PENCEGAHAN HEALTHCARE ASSOCIATED INFECTIONS DI GEDUNG FRESIA RUMAH SAKIT UMUM PUSAT DR. HASAN SADIKIN BANDUNG - Mokhamad Sandi Haryanto (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2022)
Healthcare Associated Infections are infections that occur in patients and medical personnel in hospitals that occur during the treatment process or while working in health care facilities. Clinical signs of infection have only appeared at least 3x24 hours since the start of treatment. In developing countries including Indonesia, the average prevalence of nosocomial infections is around 9.1% with a variation of 6.1% - 16%. The purpose of this study was to determine the relationship between the knowledge of nurses and the behavior of preventing Healthcare Associated Infection in the Fresia Building, dr. Hasan Sadikin Bandung. The research method uses descriptive quantitative with a cross sectional study approach with a total sampling of 75 respondents. The results showed that 75 respondents had high knowledge, which was 98.7%, and had high behavior, which was 93.3%. In conclusion, the statistical test results obtained the value of Sig. (2-tailed) = 0.000 means <0.05 which indicates that there is a significant relationship between the level of knowledge and the prevention behavior of Healthcare Associated Infections.